Asymmetric Hubbard model within generating functional approach in dynamical mean field theory - Stasyuk, I.V.; Hera, O.B. (Condensed Matter Physics, 2006)
In the paper a new analytic approach to the solution of the effective single-site problem in the dynamical mean field theory is developed. The approach is based on the method of the Kadanoff-Baym generating functional in the form developed by Izyumov et al. It makes it possible to obtain a closed equation in functional derivatives for the irreducible part of the single-site particle Green’s function; the solution is constructed iteratively. As an application of the proposed approach the asymmetric Hubbard model (AHM) is considered. The inverse irreducible part Ξ⁻¹σ of the single-site Green’s function is constructed in the linear approximation with respect to the coherent potential Jσ. Basing on the obtained result, the Green’s function of itinerant particles in the Falicov-Kimball limit of AHM is considered, and the decoupling schemes in the equations of motion approach (GH3 approximation, decoupling by Jeschke and Kotliar) are analysed. В роботi розвивається новий аналiтичний пiдхiд для розв’язання ефективної одновузлової задачi в методi динамiчного середнього поля. Пiдхiд ґрунтується на методi твiрного функцiоналу Каданова-Бейма у формi, розробленiй в роботах Iзюмова та iн. Вiн дає можливiсть отримати замкнене рiвняння у функцiональних похiдних для незвiдної частини одновузлової функцiї Грiна частинок; розв’язки будуються iтеративним способом. В ролi застосування запропонованої схеми взято асиметричну модель Хаббарда (АМХ). Побудовано обернену незвiдну частину Ξ⁻¹σ одновузлової функцiї Грiна в лiнiйному наближеннi за когерентним потенцiалом Jσ. Виходячи з отриманого результату, розглянено функцiю Грiна рухомих частинок у границi Фалiкова-Кiмбала АМХ, проаналiзовано схеми розщеплень у рiвняннях руху для одновузлової функцiї Грiна (наближення GH3, розщеплення ЄшкеКотляра).